Determination of modeled luminosity-based and pressure-based ignition delay times of turbulent spray combustion. (December 2016) - Samimi Abianeh, O.; Curtis, N.; Sung, Chih-Jen
Highlights: Modeling of Turbulent spray combustion of n-dodecane. Modeled and measured pressure-based ignition delay were compared Luminosity-based ignition delay was determined using three different methods. Hydroperoxyalkyl history can be used to determine luminosity-based ignition delay. Abstract: Turbulent spray combustion of n-dodecane was studied computationally in a constant volume combustion chamber, with a special emphasis on determining an analogous definition of experimental luminosity-based ignition delay time for computational fluid dynamics simulations. This modeling study was conducted over a range of initial combustion chamber temperatures varying from 900 K to 1200 K and gas density of 22.8 kg/m 3, using Large Eddy Simulation of turbulence, multizone combustion model, adaptive mesh refinement, and a skeletal n-dodecane chemical kinetic model. The spray and jet penetrations, combustion chamber pressure rise, fuel vapor mass fraction, and flame lift-off length were modeled and compared with the experimental data. Among all of the key species and spray characteristics studied, the modeled ignition delay times based on the n-dodecane vapor penetration, the hydroperoxyalkyl (QOOH) and hydroxyl (OH) mass history were shown to better match with the experimental results, and hence can be utilized in simulations to accurately determine the luminosity-based ignition delay times.